Βenthic hydrozoan assemblages as potential indicators of environmental health in a Μediterranean Μarine protected area - YILMAZ, IZZET NOYAN; MARTELL, LUIS; TOPCU, NUR EDA; ISINIBILIR, MELEK (Mediterranean Marine Science, 2020)
The comparative study of marine benthic hydrozoan assemblages can improve our understanding of environmental and ecological conditions in marine protected areas (MPAs) such as the large Mediterranean MPA of Datça-Bozburun, where important prospects for future intensive tourism development exist. The analysis of such assemblages may help managers detect changes in important parameters of ecosystem health within this MPA. In this study we compared the hydrozoan assemblages occurring on hard (rocky) and soft (Posidonia meadows) bottoms from stations belonging to three different conditions: i) small marinas (medium anthropogenic impact), ii) yacht stopovers (low impact), and iii) unspoiled sites (no impact) in the southern part of the Datça Peninsula during summer and winter 2015 and 2016. Significant differences in the structure, species composition and richness of benthic hydrozoans among the sampling sites were detected. In both seasons, hydroid assemblages in medium-impact sites significantly differed from little-impact and no-impact sites in terms of qualitative composition. Large structural species were widely represented in all hard-bottomed sampling sites, but small inconspicuous taxa with diverse life histories were much less abundant at the medium impacted sites. Species richness and diversity in Posidonia meadows was much higher in little- and no-impact sites, where highly specific hydroid epibionts were abundant.